Plant-based films and hydrogels for wound healing - Lopes, Ana I. (2024)
Skin is constantly exposed to injury and infectious agents that can compromise its structural integrity and cause wounds. When this occurs, microorganisms from the skin microbiota and external bacteria and fungi can penetrate the wound and cause an infection, which complicates the healing process. Nowadays, there are several types of wound dressings available to treat wounds, some of which are incorporated with antimicrobial agents. However, the number of microorganisms resistant to these substances is rising. Therefore, the search for new, natural alternatives such as essential oils (EOs) and plant extracts (PEs) is on the rise. However, these substances present some limitations (poor bioavailability and poor target capacity), which limits their efficiency. Their incorporation in formulations in the form of films and hydrogels (HGs) can help to overcome these issues and may be a potential alternative to the current treatments. HGs and films incorporated with PEs and EOs have antimicrobial activity, promote the viability of skin cells and fibroblast migration, and are non-toxic and biocompatible. This review discusses the use of films and HGs for the topical delivery of EOs and PEs for wound treatment and their formulations as effective wound dressings, while debating some mechanisms and biological properties to elucidate their presumptive clinical relevance and possible applications.